PENGUATAN LEMBAGA BUMNAG PURO NAGARI KOTO LAWEH, KECAMATAN LEMBANG JAYA, KABUPATEN SOLOK - Nidia Anggreni Das; Edi Firnando; Yulhan Yuhan; Yendi Putra; Rita Dwi Putri; Witra Maison; Lili Wahyuni; Siska Yulia Defitri; Juita Sukraini; Aldo Sofari (JURNAL PENGABDIAN MANDIRI, 2022)
According to PP 11 of 2021, Village-Owned Enterprises, hereinafter referred to as Village BUM, are legal entities established by villages and/or together with villages to manage businesses, utilize assets, develop investment and productivity, provide services, and/or provide other types of businesses for the maximum welfare of the village community. BUM-Nag is a form of alternative business entity that needs special attention and is developed to improve the nagari economy, with the aim that the birth of Bum-Nag can create new economic resources for Nagari that are used for the economic welfare of the Nagari people. The service activity aims to contribute thoughts and counseling on strengthening the BUM-Nag institution as a form of effort in improving the nagari economy. Service activities were carried out in Nagari Koto Laweh, Lembang Jaya District, Solok Regency. Community service uses the Group Discussion Forum (FGD) method, assistance and counseling carried out by delivering BUMNag Institutional material by UMMY Solok Lecturers. The result to be achieved in this service activity is to improve science, understanding and and the ability or capacity of Nagari's apparatus to strengthen the institution and management of BUM-Nag as a form of efforts to improve the Nagari economy.